An Experimental Study on Deformation Fractures of Fissured Rock around Tunnels in True Triaxial Unloads - Meng Wang; Zheming Zhu; Jun Xie (Advances in Materials Science and Engineering)
Joints and cracks are frequently encountered in underground rock mass. During the process of tunnel excavations or other underground construction, the rock will be exposed suddenly, and such sudden unloading process will cause crack expansion and destabilize the rock structure. In order to investigate the crack behaviour during this process, a true triaxial loading apparatus with a computer-controlled electrohydraulic servosystem was established, and a series of true triaxial loading and unloading experiments was conducted by using concrete specimens containing inclined cracks with inclinations of 15°, 30°, 45°, 60°, and 75°. The stress-strain behavior and the failure property of rock models during unloading process were obtained, and, additionally, the coefficient of brittle stress drop was investigated. The uniaxial compression tests were simulated by using finite element method.